2020
DOI: 10.1210/clinem/dgaa779
|View full text |Cite
|
Sign up to set email alerts
|

Use of Preoperative Imaging in Primary Hyperparathyroidism

Abstract: Context Preoperative imaging is performed routinely to guide surgical management in primary hyperparathyroidism, but the optimal imaging modalities are debated. Objective Our objectives were to evaluate which imaging modalities are associated with improved cure rate and higher concordance rates with intraoperative findings. A secondary aim was to determine whether additive imaging is associated with higher cure rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…A total of 23 studies investigated PHPT patient populations before initial parathyroid surgery. 8,[10][11][12][13][14][15][16][17][19][20][21][22][23][24][26][27][28][29][30][31][32][33] However, 3 studies reported specifically on patients with PHPT with recurrent/reoperative disease. 9,25,28 Characteristics of parathyroid disease are summarized in eTable 2 in the Supplement.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 23 studies investigated PHPT patient populations before initial parathyroid surgery. 8,[10][11][12][13][14][15][16][17][19][20][21][22][23][24][26][27][28][29][30][31][32][33] However, 3 studies reported specifically on patients with PHPT with recurrent/reoperative disease. 9,25,28 Characteristics of parathyroid disease are summarized in eTable 2 in the Supplement.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In subsets of patients with single-gland parathyroid disease (SGD), sensitivity of 4D-CT localization ranged from 58% to 92%, contrasted with 43% to 67% in patients with multigland parathyroid disease (MGD). 10,12,17,23,32,33 DECT & PET/CT Only 5 studies investigated the relatively novel application of DECT and PET/CT for PHPT patients. The mean values for DECT localization were 77.5% accuracy, 87.0% sensitivity, and 88.5% PPV.…”
Section: D-ctmentioning
confidence: 99%
See 2 more Smart Citations
“…They encouraged the main utility of 4DCT is in the setting of negative 99m Tc-sestamibi SPECT/CT. In 28 patients where 4DCT was performed out of 1485 total adult patients in their retrospective cohort study, Broome et al suggested 4DCT performed better than 99Tc-sestamibi SPECT in single adenomas and better than other modalities investigated for MGD and double parathyroid adenoma (163). These findings were however underpowered and compared 4DCT to SPECT rather than SPECT/CT.…”
Section: Comparative Effectivenessmentioning
confidence: 99%